2011
DOI: 10.1038/modpathol.2011.104
|View full text |Cite
|
Sign up to set email alerts
|

The morphologic spectrum and clinical significance of light chain proximal tubulopathy with and without crystal formation

Abstract: The renal diseases most frequently associated with myeloma include amyloidosis, monoclonal immunoglobulin deposition disease, and cast nephropathy. Less frequently reported is light chain proximal tubulopathy, a disease characterized by j-restricted crystal deposits in the proximal tubule cytoplasm. Light chain proximal tubulopathy without crystal deposition is only loosely related to the typical light chain proximal tubulopathy, and little is known about this entity. A search was performed of the 10 081 nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
124
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 29 publications
13
124
1
1
Order By: Relevance
“…Larsen et al (10) studied 10,081 cases of renal biopsy specimens and found that there were only 13 cases of proximal tubular damage caused by light chain proteins, including 3 cases with crystalloid formation (2 of 3 cases showing κ light chains). In this previous study, the diagnosis of malignant plasma cells could not be established for some patients at the time of renal biopsy, although the patients were diagnosed later in a follow-up study with the gradual emergence of corresponding clinical manifestations (10). In contrast, it is very rare to present large quantities of crystalline inclu- sions deposited in podocytes and only 10 cases have been reported to date (2,5,6,(11)(12)(13)(14)(15)(16)(17) (Table).…”
Section: Discussionmentioning
confidence: 96%
“…Larsen et al (10) studied 10,081 cases of renal biopsy specimens and found that there were only 13 cases of proximal tubular damage caused by light chain proteins, including 3 cases with crystalloid formation (2 of 3 cases showing κ light chains). In this previous study, the diagnosis of malignant plasma cells could not be established for some patients at the time of renal biopsy, although the patients were diagnosed later in a follow-up study with the gradual emergence of corresponding clinical manifestations (10). In contrast, it is very rare to present large quantities of crystalline inclu- sions deposited in podocytes and only 10 cases have been reported to date (2,5,6,(11)(12)(13)(14)(15)(16)(17) (Table).…”
Section: Discussionmentioning
confidence: 96%
“…Two series of patients manifesting this pattern of proximal tubulopathy have been published in the literature. 48,49 Although both j and k light chains have been documented to occur in association with this variant, a predominance of j light chains has been observed. Those light chains associated with interstitial inflammatory reactions are also delivered to the lysosomal compartment, and catabolism is also impaired.…”
Section: Metabolism Of Light Chains In Proximal Tubules/handling Of Pmentioning
confidence: 99%
“…The manifestations associated with unique cytoplasmic inclusions, which are generally crystalline in proximal tubular cells, represent the lesion that has been recognized in the literature as light chain Fanconi syndrome 49,[53][54][55][56][57] (Figures 13 through 16). Clinically, it is characterized by progressive renal dysfunction with defects in proximal tubule reabsorption and typically exhibits a rather slow, protracted clinical course.…”
Section: Metabolism Of Light Chains In Proximal Tubules/handling Of Pmentioning
confidence: 99%
“…Both LC and kLC are found within PTEC deposits, although crystalline-like deposits almost exclusively are formed by k chains (certain subtypes, such as subtype Vk1 LC have been identified as having particular properties to form crystals). 5,9 It has been postulated, that the mutations of the gene encoding CDR-L1 (complementarity-determining region L1 of LCs, contributing to formation of immunoglobulin antigen-binding site) may facilitate resistance to proteases, causing the accumulation of LC in PTEC lysosomes where they serve as a nidus for crystal formation. Such a resistance to proteolysis seems to be a peculiar characteristic of LC involved in the pathophysiology of Fanconi syndrome, since it was never documented in cast nephropathy patients or myeloma patients without renal involvement.…”
Section: Discussionmentioning
confidence: 99%